Penerapan Pasal 54 Ayat (1) KUHP oleh Hakim dalam Menjatuhkan Putusan Pemidanaan - Pratama, M. Ilham Wira (Universitas Muhammadiyah Yogyakarta, 2024)
Sentencing guidelines are one of the main things that from the substance of criminal law reform in the Indonesian Criminal Code. With the stipulation of sentencing guidelines in the Indonesian Criminal Code, judge have clear guidelines, especially regarding matters that must be considered in handing down a sentence in the form of a sentence, but this raises questions regarding the judge’s obligation to follow these guidelines, considering that judges have freedom in handing down decisions. The aim of this research is to find out how to apply the things that must be considered by judges as determined by the Criminal Code in their decisions in the form of punishment. The research method used in this research is normative research, with a statutory and conceptual approach. The research results show that judges are obliged to apply all the provisions mentioned in Article 54 paragraph (1) of the Criminal Code in the criminal decisions they hand down, and if the provisions in question are not implemented then the decision is null and void